Metal matrix composites for automotive components in depth case study : Development of automotive brake disc - Fatchurrohman, Nanang; Shamsuddin, Sulaiman (Elsevier, 2021)
In today’s overwhelming competition, the knowledge on product development represents a very significant aspect for companies to survive in the market. Among these sectors is the automotive industry, where it is one of the most fast growing, highly demanding and stiff competition marketplaces. Intensive research in this field is targeted to produce light weight and high performance components which can increase fuel efficiency and sustainability of an automobile. One of the recent avenues is the investigation of increased performance engineered materials to replace the conventional materials. In this study product development of engineered material - metal matrix composites (MMCs) component is explored. To achieve a sound product development, new integrated product development framework which utilised simultaneous approach is developed. It presents an implementation of simultaneous approach (SA) and an analytical network process (ANP) to form a new rating method as part of the manufacturing process and material analysis in the product development environment. The proposed procedure is referred to as a concurrent network (CN). It is planned for CN to carry out simultaneous analysis of all aspects of product elements by using SA strategy. CN enables interdependence and interrelationship analysis between product elements by implementing ANP. CN is utilised for the manufacturing process and material analysis of a metal matrix composites (MMCs) automotive component which is the brake disc. The results show that by using CN, all the product parameters can be analysed comprehensively and the importance weights of the product parameters with regard to the MMCs brake disc performance are obtained. It is concluded that in the manufacturing process cluster the primary process parameter has the highest score, while in the material cluster the ranking is dominated by mechanical properties. This means that these sub-conceptual parameters are the most important ones to consider in order to achieve the required performance of the product.